O ethos midiatizado de Marco Feliciano: uma análise da formação institucional de discursos sobre o controle do ethos privado - Castilho, Marina Martinuzzi (2019)
The present dissertation seeks to investigate how the mediated ethos of the pastor and federal deputy Marco Feliciano reproduces discourses on the control of the private ethos. From the media biopolitical religion intersection, we construct a theoretical path in order to identify the institutional dimension of the subject, based on authors such as Berguer and Luckmann (2004), Foucault (1988, 1999a) and Duarte (2005). By characterizing religious and political institutional brands in the perspective of modern and ongoing transformations in Western society, we perceive structural attention to private conduct and, above all, to human sexuality. In the pretension of highlighting the presence and discursive performance of this social actor, we describe its relations and movements according to the formation of an ethos mediated (Sodré, 2010) and discursive own, acclimated by political, religious and mediatic interpellation. Understanding the eminent historicity and control in the social construction of reality, we try to analyze how the present manifestation of Feliciano in his social media triggers discourses of control over private conduct. We specified our look around the YouTube channel and #OurFamilyDeserveRespect for verifying a campaign used by the pastor and federal deputy in which he asked to share the videos with the hashtag a message that was also fixed in his other channels in the networks. The centrality assumed by Feliciano in these videos is what leads us to the empirical cut: proximity to the public and informal language about recent events moves the actor to a specific communication situation (CHARAUDEAU, 2007), where religious, political and media discourse in interpellation. Thus, the analysis of the discourse composes our methodology from the operationalization of the ethos and this in contact with processes constructed by the mediatization and the specific communicative situation that involves Marco Feliciano. As a result of this research, it is possible to identify the process of mediatization as another structuring element in the transformation of modern, discursive and cultural events. We also identify in the current political moment, especially from the practice of deputies such as Marco Feliciano, a complex scenario in which liberal democratic regimes, associated with mediated and modernizing logics, dialectically construct with individuals and institutions, new discourses of control and surveillance of bodies and behaviors.